AMPK and CAMKK activation participate in early events of Toxoplasma gondii-triggered NET formation in bovine polymorphonuclear neutrophils - Conejeros, Iván; Velásquez, Zahady D.; Espinosa, Gabriel; Rojas-Baron, Lisbeth; Grabbe, Magdalena; Hermosilla, Carlos; Taubert, Anja (Frontiers in Veterinary Science, 2025)
Toxoplasma gondii is an obligate intracellular apicomplexan parasite that infects humans, eventually causing severe diseases like prenatal or ocular toxoplasmosis. T. gondii also infects cattle but rarely induces clinical signs in this intermediate host type. So far, the innate immune mechanisms behind the potential resistance of bovines to clinical T. gondii infections remain unclear. Here, we present evidence on sustained activation of bovine polymorphonuclear neutrophils PMN by T. gondii tachyzoites, which is linked to a rise in cytoplasmic calcium concentrations, an enhancement of calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK) and AMP-activated protein kinase (AMPK). NETosis is a specific form of programmed cell death, characterized by the release chromatin from the nucleus to the extracellular space resulting in formation of neutrophil extracellular traps (NETs). NETs can kill and entrap pathogens. In our experiments, NETosis was triggered by T. gondii, and this effector mechanism was enhanced by pre-treatments with the AMPK activator AICAR. Moreover, tachyzoite-mediated bovine neutrophil DNA release depended on MAPK- and store operated calcium entry- (SOCE) pathways since it was diminished by the inhibitors UO126 and 2-APB, respectively. Overall, we here provide new insights into early polymorphonuclear neutrophils responses against T. gondii for the bovine system.